The Diversity of Pteridophyta at Mountain Telomoyo as Biology Learning Resources - Muhammad Radian Nur Alamsyah; Sekar Jati Pamungkas (Indonesian Journal of Biology Education, 2020)
The identification and utilization of pteridophyta diversity in the Telomoyo mountain area in learning activities has not been implemented. On the other hand, Biology as a science subject needs to be presented through scientific learning to encourage the development of students' science process skills. The type of learning resource by utilization is the right type to be used in scientific learning. These learning resources are found mainly in nature. Based on this, this study aims to identify the diversity of pteridophyta in Mount Telomoyo and to analyze their feasibility as a source of Biology learning at the high school. This study uses a descriptive exploratory method. The observation plot was determined to be 2 meters wide from the right and left side  along the climbing route, using a purposive sampling technique. Analysis of learning resources using benchmarks by Djohar (1974). The results, there are 13 species of pteridophyta which can be classified into 12 genera, 10 families, 4 orders, and 2 divisions. Biology material that is appropriate for the application of learning resources is the Scope of Biology with a 75% suitability level. The results of the feasibility analysis of learning resources generally obtained a very feasible category (87%).